2019
DOI: 10.1159/000500011
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of <b><i>Lysimachia christinae Hance</i></b> Extract Fractions on Endothelium-Dependent Vasodilatation

Abstract: Background: Endothelium-dependent dilatation is a predictor for vascular function. NADPH oxidase-derived O2 can inactivate nitric oxide and induce vascular injury. Method: The crude ethanolic extract of Lysimachia christinae Hance were separated out 4 fractions of different olarities by petroleum ether, ethyl acetate, n-butanol (NB), and aqueous. The endothelial integrity was appraised by vascular tension measurement. Dihydroethidium was utilized to observe the vascular reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Extracts of these plants are known to contain polyphenols [37] and saponins [38]. It has been shown that extracts of species of the Lysimachia genus have antioxidant [39][40][41], anthelmintic [42], antimicrobial [43], and endothelioprotective effects [41], and they can improve the vasodilating function of the endothelium [44], inhibit lipogenesis processes [36], and exhibit therapeutic effects on neurodegenerative diseases [45].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of these plants are known to contain polyphenols [37] and saponins [38]. It has been shown that extracts of species of the Lysimachia genus have antioxidant [39][40][41], anthelmintic [42], antimicrobial [43], and endothelioprotective effects [41], and they can improve the vasodilating function of the endothelium [44], inhibit lipogenesis processes [36], and exhibit therapeutic effects on neurodegenerative diseases [45].…”
Section: Introductionmentioning
confidence: 99%
“…Among various types of TCM for the treatment of urolithiasis, Lysimachia christinae Hance (Jin Qian Cao), a herbaceous plant of the family Primulaceae, is widely used for treating hepatobiliary lithiasis, urolithiasis, biliary calculus, etc . On account of its various medicinal values as an herb, it has been increasingly investigated for its chemical constituent analyses and therapeutic potential. Gallic acid (GaA), a dietary polyphenolic acid that has antioxidative, antibacterial, and anticancer properties, is one of the most important polyphenols in Jin Qian Cao . However, the effect of gallic acid on the formation of kidney stones, specifically the crystallization of calcium oxalate, has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Rutin, a natural flavone derivative, has powerful antioxidant capacity by scavenging free radicals and chelating metals in vivo and in vitro (Javed et al, 2012;Kamalakkannan, Stanely, & Prince, 2006;Magalingam, Radhakrishnan, & Haleagrahara, 2013). Previous studies have shown that the components of LHE may contribute to its potent antioxidant effects by preventing hydrogen peroxide (H 2 O 2 )-induced oxidative stress (Wu et al, 2018;Zhang, Liu, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Rutin, a natural flavone derivative, has powerful antioxidant capacity by scavenging free radicals and chelating metals in vivo and in vitro (Javed et al., 2012; Kamalakkannan, Stanely, & Prince, 2006; Magalingam, Radhakrishnan, & Haleagrahara, 2013). Previous studies have shown that the components of LHE may contribute to its potent antioxidant effects by preventing hydrogen peroxide (H 2 O 2 )‐induced oxidative stress (Wu et al., 2018; Zhang, Liu, 2019). Our previous study also revealed that LHE has high antioxidant activities as tested by 2,2′‐azino‐bis‐3‐ethylbenzothiazoline‐6‐sulfonic acid (ABTS) and 2,2′‐diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging assays, ferric reducing antioxidant power (FRAP), and reducing power assay (Lee, 2019).…”
Section: Discussionmentioning
confidence: 99%